PEMBUATAN PEKTIN DARI KULIT MARKISA KUNING (Passiflora edulis flavicarpa) YANG DIMODIFIKASI - Riyan Riski Sarandi; Yusro Alhusna; Setiaty Pandia (Jurnal Teknik Kimia USU, 2015)
Passion fruit (Passiflora edulis flavicarpa) peel, a waste from yellow passion fruit industry could be utilized to extract pectin. The objectives of this study were to extract and modify yellow passion fruit pectin from HMP (High Metoxyl Pectin) to LMP (Low Metoxyl Pectin) and compare characteristic both of them. This research was conducted in pectin extraction and then modify pH of pectin used natrium hydroxide and chloric acid. The result of this research showed that modified pectin succeded to decrease degree of esterification from HMP to become LMP. Modified pectin had a brighter color or not too browny and no aroma. Function group analysis showed that shift in peaks in FTIR confimed a decrease of number methylated –COOH group. The resulting pectins also gelled by charge compensation with acid. It was found a new function group in modified pectin, which was of C=C (aromatic) group. The yield of pectin by extracting was 2,54 % and yiled of pectin after modifying was 94,73 %.